2021
DOI: 10.1038/s43587-021-00149-w
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease modification mediated by bone marrow-derived macrophages via a TREM2-independent pathway in mouse model of amyloidosis

Abstract: The contributions of disease-associated microglia (DAM) and in ltrating monocyte-derived macrophages (MDM) to Alzheimer's disease (AD) are still controversial. Here, using Trem2 −/− 5xFAD DAM-de cient mice, we addressed this issue by targeting the programmed cell death ligand-1 (PD-L1) immune checkpoint, shown to modify AD via MDM recruitment. Treating Trem2 −/− 5xFAD mice resulted in cognitive improvement, rescue of synapses, and reduction of soluble-amyloid beta (Aβ) 1−42 , with no effect on insoluble Aβ 1−4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…In 2019, Schwartz's group showed that immune checkpoint blockade targeting the PD-1/PD-L1 pathway might have beneficial results in a tau-driven disease model resembling Alzheimer's disease (AD). The use of PD-L1 blocking antibodies resulted in increased immunomodulatory monocyte-derived macrophages within the brain parenchyma, which ultimately led to the modification of brain pathology and the restoration of cognitive performance ( 59 , 60 ).…”
Section: Pd-1 Role During Neuroinflammationmentioning
confidence: 99%
“…In 2019, Schwartz's group showed that immune checkpoint blockade targeting the PD-1/PD-L1 pathway might have beneficial results in a tau-driven disease model resembling Alzheimer's disease (AD). The use of PD-L1 blocking antibodies resulted in increased immunomodulatory monocyte-derived macrophages within the brain parenchyma, which ultimately led to the modification of brain pathology and the restoration of cognitive performance ( 59 , 60 ).…”
Section: Pd-1 Role During Neuroinflammationmentioning
confidence: 99%
“…In 2016, our research team proposed an immunotherapy that targets the programmed death (PD)‐1/PD‐L1 inhibitory immune checkpoint pathway (Baruch et al, 2016) (Figure 1c), as a means of unleashing peripheral immunity and triggering a cascade of immunological events, ultimately leading to improvement of brain function in both Aβ and tau‐driven mouse models of dementia (Baruch et al, 2016; Ben‐Yehuda et al, 2021; Rosenzweig et al, 2019; Xing et al, 2021). Targeting the PD‐1/PD‐L1 pathway initiates an immune response in the periphery that drives the recruitment of specific immune cell populations towards the brain, including T regulatory cells and macrophage scavenger receptor 1 (MSR1)‐expressing bone marrow‐derived macrophages that allow the removal of aggregated misfolded proteins (Frenkel et al, 2013), rescuing synapses, protecting neurons, and arresting cognitive loss (Dvir‐Szternfeld et al, 2021; Ben‐Yehuda et al, 2021; Rosenzweig et al, 2019) (Figure 1c). Such an approach is supported by the demonstration that interferon‐γ signalling mediates the mobilization of inflammation‐resolving immune cells into the brain (Baruch et al, 2016) through activation of the choroid plexus epithelium (Kunis et al, 2013; Shechter et al, 2013).…”
Section: Immune‐based Therapies: Current Challenges and New Opportuni...mentioning
confidence: 99%
“…The cellular origin of DAM and their function have been recently studied by several independent teams. A work from our group, using a bone marrow chimeric mouse model (Dvir-Szternfeld et al, 2021), and a study that used a fate-mapping reporter mice (Reed-Geaghan et al, 2020), unequivocally demonstrated that bone marrow-derived macrophages do not contribute to the DAM cell pool. Yet, facilitating the recruitment of monocyte-derived macrophages into the brain has been shown to be of utmost importance in fighting AD (Ben-Yehuda et al, 2021;el Khoury et al, 2007;Rosenzweig et al, 2019).…”
Section: Targeting Microglia the Brainresident Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations